A perspective on arthroscopic treatment for anterior ankle impingement syndrome: clinical research insights - Zong, Long-Ze; Feng, Yong; Bai, Dong-Yu (Frontiers in Surgery, 2026)
IntroductionAnterior ankle impingement syndrome (AAIS) is a degenerative condition that causes anterior ankle pain and limited dorsiflexion, especially in athletes. It results from either osseous (osteophytes) or soft tissue (synovial hypertrophy, fibrosis) pathology.MethodsAlthough conservative treatments offer temporary relief, arthroscopic surgery has become the preferred approach due to its minimally invasive technique and surgical precision.ResultsCurrent evidence shows 80%–90% success rates, with significant improvements in visual analog scale scores (mean reduction of 4.1 points) and American orthopedic foot & ankle society scores (mean increase of 28 points), along with low complication rates (2%–7%). However, outcomes are closely linked to the severity of pre-existing osteoarthritis, with 93% success in non-arthritic joints compared to 53% in cases with moderate osteoarthritis. Key research limitations include heterogeneous study designs, small sample sizes, and a lack of long-term data (only 18.6% of studies report ≥5-year follow-up).DiscussionFuture research should focus on standardizing outcome measures, assessing the cost-effectiveness of advanced techniques, and establishing evidence-based protocols for patient selection and rehabilitation. These efforts will help optimize surgical decision-making and enhance long-term outcomes for patients with AAIS.